The redesign of cities for urban warfare resilience and deterrence after the Russo-Ukrainian war of 2022 - Jordan Shishovski; Sasho Blazhevski; Ivona Mileva (University American College Skopje, 2022)
Architecture and urban planning have always been deeply involved in the design and building of defense facilities because cities have been centers of economic, political and military power since the dawn of civilization. The famous Roman architect Vitruvius was himself a military engineer before engaging with architecture. Defense walls, towers and other fortifications dominate every pre-modern city around the world. The advance in modern technology, artillery and airpower fundamentally changed this. Traditional fortifications were no match for modern firepower. Thus, military conflicts spread throughout the territory drawing the creation of new kinds of fortifications - such as bunkers and trenches. With industrialization, however, cities have become even more important as economic, industrial and political powerhouses. Their symbolic significance also is not negligible in modern conflicts and is often crucial in military planning. The battle of Stalingrad of 1942-3 stands out in this respect. With the more robust global economy, vulnerable to wider disruptions, and with new advanced precision firepower, modern military conflicts are bringing the war back to the city. The important urban centers are becoming the focus for new urban warfare. The current war in Ukraine is essentially urban warfare. Urban warfare faces both the defending and invading armies with hard choices and very specific challenges. This brings forth a need for a rethinking of the modern urban and public-architecture practices and design choices as well as urban development policies. The goal of this presentation and paper will be to bring the attention of architectural theory, and urban and architectural design to this important topic and make theoretical and policy recommendations for the lessons learned from the urban warfare of the current Russo-Ukrainian war of 2022. We aim in contributing toward a redesign of urban centers with defense, and consequently military deterrence in mind.
Keywords: 330; urban warfare; Ukraine; war; fortification; architecture; urban planning